Potential exposure to silver nanoparticles during spraying preparation for air-conditioning cleaning - Elżbieta Jankowska; Joanna Łukaszewska (Nofer Institute of Occupational Medicine, 2013)
Background: Unique properties of engineered nanomaterials (ENMs) and products made of them have contributed to a rapid progress in the production and application of ENMs in different branches of industry and in factories with different production scale. Bearing in mind that nano-objects (nanoplates, nanofibres, nanoparticles), emitted during ENM production and application, can cause many diseases, even those not yet recognized, extensive studies have been carried all over the world to assess the extent of exposure to nano-objects at workstations and related health effects in workers employed in ENM manufacture and application processes. Material and Methods: The study of potential exposure to silver nanoparticles contained in the preparation for airconditioning cleaning (Nano Silver from Amtra Sp. z o.o.) involved the determination of concentrations and size distribution of particles, using different devices, allowing for tracing changes in a wide range of dimensions, from nano-size (10 nm) to micrometrsize (10 µm), of the particles which are usually inhaled by humans. Results and Conclusions: The results of the study shows that even during a short-term spraying of Nano Silver preparation (for 10 s) at the distance of 52 cm from the place of preparation spraying - particles of 10 nm-10 µm can be emitted into in the air. During a three-fold preparation spraying in similar conditions differences in concentration increase were observed, but in each case the particles remained in the air for a relatively long time. Med Pr 2013;64(1):57-67